Peran Trait Kepribadian Conscientiousness dan Iklim Sekolah Dengan Student Engagement SMA - Ridha syafiqah zahra; Mustamira Sofa Salsabila; Citra Wahyuni (Universitas Muhammadiyah Gresik, 2025)
Background: Student engagement in learning is influenced by various factors, including the personality trait of conscientiousness and school climate.Objective: This study aims to analyze the influence of these two factors on student engagement in high schools in Bandar Lampung. Method: This research uses a quantitative approach involving 394 students with Accidental Sampling as the sampling technique. Data collection is done using a student engagement scale (Y), conscientiousness personality trait scale (X1), and school climate scale (X2). Data analysis in this study uses multiple regression with the assistance of JASP software. Results: The study shows that the conscientiousness personality trait has a significant influence on student engagement, while the school climate contributes to increasing motivation and student engagement. The regression analysis shows an R² value of 0.724, meaning that 72.4% of the variation in student engagement can be explained by conscientiousness and school climate, while 27.6% is influenced by other factors not examined in this study. Conclusion: The development of character and a positive school environment can improve student engagement. The results are expected to serve as recommendations for educators and policymakers in designing more effective learning strategies.